Aspects Of Spirituality And Religiusity In Patients End Stage Renal Disease (ESRD) - Muhammad Putra Ramadhan; Krisna Yetti (Universitas Respati Yogyakarta, 2020)
Comprehensive and holistic nursing care by professional nurses is continuously improved, especially nursing care in ESRD patients. This has an impact on the importance of knowing the potential to be revamped so that the poor quality of life in ESRD patients can be enhanced one of the aspects of spirituality and religiusity included in the comprehensive and holistic. The aim of this study was to study the aspects of spirituality and religiusity in End Stage Renal Disease (ESRD) patients. This study uses a Litelature review was chosen as the method used for this study by collecting litelature from ProQuest, Wiley Online, and Scientdirect databases using the keywords